α and γ Alumina Spheres for Azo Dye (Allura Red) Removal from Aqueous Media - Torres Perez, Jonatan (2022)
Allura red or Red 40 (R40) is a dye widely used in the food, textile, and pharmaceutical industries; it is considered dangerous because it is soluble in water, and it has high toxicity and resistance to natural degradation. Several advanced wastewater treatments have been shown to be effective for R40 removal but some of them present disadvantages such as by-products obtention, high energy consumption, and high cost of the reactants used in the removal process. In the present work, α-Alumina (Alu) and γ-Alu spheres were synthesized by the encapsulation method. The prepared spheres were characterized by FT-IR, XRD, SEM/EDS, and SBET, and it was determined the presence of only inorganic bonds from ceramic material, and the amorphous alumina was observed in spheres with a smooth and uniform surface and with pores. R40 adsorption kinetics and isotherms were performed, as well as material regeneration for consequent sorption cycles. Sorption tests for R40 removal were carried out under different conditions of initial concentration, pH value, and the presence of interfering ions. The maximal sorption capacity of the synthetized α- and γ-Alu spheres were situated between 0.1765 and 18.9865 mg/g. Different kinetic and isothermal equations were applied and finally, the experimental data was described by Elovich and Freundlich models. The γ-Alu spheres after five heat treatment regeneration cycles showed stable behavior and potential re-use in new sorption processes with R40 removal >97.7% at pH 3 and >85.6% at  =10 mg/L. The obtained results showed that the γ-Alu spheres are novel, alternative, and sustainable synthesized materials for the advanced treatment of wastewater by adsorption process for the removal of Allura red azo dye in aqueous media.